Does Functional Outcome Improve with Time Postsurgery for Hirschsprung Disease? - Aworanti, Olugbenga Michael; McDowell, Dermot Thomas; Martin, Ian Michael; Quinn, Feargal (European Journal of Pediatric Surgery, 2016)
Purpose Constipation and incontinence are significant problems following pull-through surgery for Hirschsprung disease (HD). There is evidence that these problems improve with time. However, there is also evidence showing no improvements and furthermore, significant long-term data are lacking for the newer endorectal pull-through. We aim to determine if there is clinical evidence that show improvements in functional outcomes with time after an endorectal pull-through surgery for HD.Methods We utilized the validated pediatric incontinence and constipation scoring system (PICSS) to score 51 consecutive children 3 months to 15 years posttransabdominal or transanal endorectal pull-through for HD. Cases of total colonic aganglionosis and Down syndrome were excluded. PICSS scores below the age-specific lower limit 95% confidence interval scores represent incomplete continence or constipation, respectively. We performed linear regression to analyze the relationship between PICSS scores and the follow-up duration and then compared the demographics of children with and without incomplete continence and constipation, respectively. Significance was set at p < 0.05.Results The median age at PICSS interview was 71 months (range, 6–191 months). Incontinence scores obtained from 42 children older than 35 months showed a positive relationship with the follow-up duration (p = 0.03). Constipation scores obtained from 51 children were unrelated to follow-up duration (p = 0.486). When demographics were compared, the continent children had longer follow-up than those with incomplete continence (mean, 111.64 vs. 69.19 months; p = 0.051), however follow-up duration did not differ in the group of constipated children compared with the nonconstipated group (mean, 61.88 vs. 71.80 months; p = 0.321).Conclusion These findings suggest that after an endorectal pull-through, improved continence should be expected with time but constipation often continues to be an ongoing problem.
Keywords: Hirschsprung disease; long-term outcome; incontinence; constipation; endorectal pull-through